2021
DOI: 10.3390/molecules26185438
|View full text |Cite
|
Sign up to set email alerts
|

Chelate Coordination Compounds as a New Class of High-Energy Materials: The Case of Nitro-Bis(Acetylacetonato) Complexes

Abstract: The existence of areas of strongly positive electrostatic potential in the central regions of the molecular surface of high-energy molecules is a strong indicator that these compounds are very sensitive towards detonation. Development of high-energy compounds with reduced sensitivity towards detonation and high efficiency is hard to achieve since the energetic molecules with high performance are usually very sensitive. Here we used Density Functional Theory (DFT) calculations to study a series of bis(acetylace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
4
1
Order By: Relevance
“…Analysis of electrostatic potential maps of the nitro-bis(acetylacetonato) complex of copper (Cu(AcAc-NO 2 ) 2 complex) showed that the value of the positive potential in the central regions of this complex (25.25 kcal/mol) is similar to the value of the electrostatic potential in the central regions of classical explosives like 2,4,6-trinitrotoluene-TNT (23.76 kcal/mol). Also, the calculated BDE value for the C-NO 2 bond of the Cu(AcAc-NO 2 ) 2 complex (59.50 kcal/mol) is very similar to the BDE value calculated for the C-NO 2 bond of the 2,4,6-trinitrotoluene (58.90 kcal/mol) [19,22]. However, the Cu(AcAc-NO 2 ) 2 complex forms coordination polymers in which monomer units are linked through nitro-groups, and this type of structure may prevent the dissociation of C-NO 2 bonds [32].…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Analysis of electrostatic potential maps of the nitro-bis(acetylacetonato) complex of copper (Cu(AcAc-NO 2 ) 2 complex) showed that the value of the positive potential in the central regions of this complex (25.25 kcal/mol) is similar to the value of the electrostatic potential in the central regions of classical explosives like 2,4,6-trinitrotoluene-TNT (23.76 kcal/mol). Also, the calculated BDE value for the C-NO 2 bond of the Cu(AcAc-NO 2 ) 2 complex (59.50 kcal/mol) is very similar to the BDE value calculated for the C-NO 2 bond of the 2,4,6-trinitrotoluene (58.90 kcal/mol) [19,22]. However, the Cu(AcAc-NO 2 ) 2 complex forms coordination polymers in which monomer units are linked through nitro-groups, and this type of structure may prevent the dissociation of C-NO 2 bonds [32].…”
Section: Introductionsupporting
confidence: 75%
“…All geometry optimizations, vibrational frequency calculations, wave function file calculations, and BDE calculations were performed using the Gaussian09 program package [38]. Geometry optimizations, vibrational frequency calculations, and electrostatic potential map calculations were performed using the M06 functional and cc-PVDZ basis sets since this level of theory showed satisfactory results when applied to similar systems [22]. BDE values were calculated using the B3LYP/6-311++G** level of theory, following the previously proposed methodology [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the calculated wave function files, electrostatic potential maps were calculated and visualized using Wave Function Analysis-Surface Analysis Suite (WFA-SAS) software [24]. Electrostatic potential maps were calculated at the M06/cc-pVDZ level of theory since this level of theory was successfully used for similar calculations in previous studies [16,25]. Critical points in electrostatic potential maps, and not in electron density were considered for the analysis.…”
Section: Methodsmentioning
confidence: 99%